2003
DOI: 10.1192/bjp.182.3.228
|View full text |Cite
|
Sign up to set email alerts
|

Paracingulate sulcus morphology in men with early-onset schizophrenia

Abstract: Since the PCS has developed at 36 weeks of gestation, these findings suggest an impaired maturation of the cingulate region during the third trimester.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
55
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(63 citation statements)
references
References 49 publications
5
55
0
Order By: Relevance
“…In contrast to the results in men, only a third of the left hemispheres of women (one study) (Yucel et al 2001) and patients with schizophrenia (two studies) (Yucel et al 2002;Le Provost et al 2003) have prominent paracingulate sulci. The Paus study found that the paracingulate sulcus was absent or prominent more often in women than men regardless of hemisphere (Paus et al 1996b).…”
Section: Introductionmentioning
confidence: 54%
“…In contrast to the results in men, only a third of the left hemispheres of women (one study) (Yucel et al 2001) and patients with schizophrenia (two studies) (Yucel et al 2002;Le Provost et al 2003) have prominent paracingulate sulci. The Paus study found that the paracingulate sulcus was absent or prominent more often in women than men regardless of hemisphere (Paus et al 1996b).…”
Section: Introductionmentioning
confidence: 54%
“…Several schizophrenia studies have previously reported deviations in sulcus anatomy, 10,35,[62][63][64][65] consistent with the common hypothesis that schizophrenia has a developmental component. 66 The deviation detected in the junction between the STS and its anterior branch suggests an early event that may have occurred between 25 and 29 weeks of gestation.…”
Section: Sulcal Junction and Brain Maturationmentioning
confidence: 63%
“…46 An asymmetric pattern, with different types in the left and right hemispheres, is common in healthy individuals. 25 On the contrary, there is a lack of such normal ACC asymmetry in patients with schizophrenia [47][48][49][50][51] and in individuals at high risk for schizophrenia. 31,[52][53][54] This observation is line with the hypothesis that anomalies of brain asymmetry are a key feature of schizophrenia.…”
Section: Discussionmentioning
confidence: 97%